Natural habitat does not mediate vertebrate seed predation as an ecosystem dis‐service to agriculture. Issue 2 (27th February 2015) - Schäckermann, Jessica; Mandelik, Yael; Weiss, Noam; von Wehrden, Henrik; Klein, Alexandra‐Maria; Kleijn, David
Summary Spillover of beneficial organisms from natural habitats to croplands can improve agro‐ecosystem services, but wildlife can also negatively influence agricultural production. When managing agricultural landscapes to conserve biodiversity, we need to understand whether the availability of natural habitats increases ecosystem dis‐services such as vertebrate seed predation to avoid risking higher costs than benefits. We studied whether vertebrates and their impact in crop seed predation are related to the percentage of natural (chaparral) and semi‐natural habitat (planted forest with native and exotic trees) in an agricultural landscape of Israel. We selected 20 almond and 20 sunflower study sites within a landscape with varying percentages of natural (0–61%) and semi‐natural (0–70%) habitats within a 1000 m radius of their surroundings. We observed birds, trapped rodents (in almond), counted seeds and noted feeding marks to obtain seed predation rates, at each site. Within the almond crops, we physically excluded birds, rodents and both to determine their relative and combined influence on seed predation. Neither vertebrate abundance nor species richness was influenced by the percentage of natural habitat. However, bird species richness increased with increasing percentage of semi‐natural habitat. Seed predation across both crops was not influenced by natural or semi‐natural habitat but increased significantly with increasing abundance and species richness of birds. This was also reflected by the exclusions of birds, vertebrates and both to the almond crop, leading to lowest seed predation when both groups were excluded. Synthesis and applications. Natural or semi‐natural habitat did not influence the agro‐ecosystem dis‐service of seed predation by birds and rodents. Policymakers should consider promoting agri‐environment schemes that include the conservation of natural habitats and the management of semi‐natural habitats adjacent to cropland to enhance agro‐ecosystem services meditated by beneficial organisms such as natural pest enemies and pollinators without fearing increased vertebrate seed predation. In order to provide more detailed management recommendations tackling the reduction of vertebrate dis‐services, their feeding behaviour, metabolic needs, behaviour patterns and local abundances should be taken into account.